Study on thermo-mechanical coupling characteristics of angle contact ball bearing with fix-position preload. Issue 6 (12th August 2019) - He, Pingping; Gao, Feng; Li, Yan; Wu, Wenwu; Zhang, Dongya
Abstract : Purpose: Under fix-position preload, the high rotation speed of the angular contact ball bearing exacerbates the frictional heat generation, which causes the increase of the bearing temperature and the thermal expansion. The high rotation speed also leads to the centrifugal expansion of the bearing. Under the thermal and centrifugal effect, the structural parameters of the bearing change, affecting the mechanical properties of the bearing. The mechanical properties of the bearing determine its heat generation mechanism and thermal boundary conditions. The purpose of this paper is to study the effect of centrifugal and thermal effects on the thermo-mechanical characteristics of an angular contact ball bearing with fix-position preload. Design/methodology/approach: Because of operating conditions, elastic deformation occurs between the ball and the raceway. Assuming that the surfaces of the ball and channel are absolutely smooth and the material is isotropic, quasi-static theory and thermal network method are used to establish the thermo-mechanical coupling model of the bearing, which is solved by Newton–Raphson iterative method. Findings: The higher the rotation speed, the greater the influence of centrifugal and thermal effects on the bearing dynamic parameters, temperature rise and actual axial force. The calculation results show that the effects of thermal field on bearing dynamic parameters are more significant than the centrifugal effect. The temperature rise and actual axial force of the bearing are measured. Comparing the calculation and the experimental results, it is found that the temperature rise and the actual axial force of the bearing are closer to reality considering thermal and centrifugal effects. Originality/value: In the past studies, the thermo-mechanical coupling characteristics research and experimental verification of angular contact ball bearing with fix-position preload are not concerned. Research findings of this paper provide theoretical guidance for spindle design.